(3aj eMGSHI GdJcGdja dCZQGV bjGS JcdaI GdEfJGL (B/s - (3eQYj, YHO GdMjs ((3GdEScfOQjI(B: s (3OGQ GdeWHhYGJ GdLGeYjI(B, s, 1998)
(3aj eGgjI GdJcdaI heVehfgG hCZQGV hCSS bjGSgG ,eGgjI GdJcdaI ,CZQGV hCSS bjGS GdJcdaI,WHjYI GdUfGYI hYfGUQ JcdaI GdGfJGL,CfXeI JcGdja GGdeQGMd,JNUjU GdJcdaI GdeTJQcI aj GdefJLGJ GdeJUdI hGdaQYjIs
Keywords: (3GdGfJGLs; (3eMGSHI GdJcGdjas